EFL educators’ engagement in professional development: Strategies and constraints - Khairiah Syahabuddin; Teuku Zulfikar; Emawati Emawati; Cut Fadhilah Alfa Karim (Studies in English Language and Education, 2026)
Professional development is essential for English as a foreign language (EFL) lecturers as they navigate educational landscapes. Within the context of Islamic higher education institutions in Indonesia, these lecturers face distinctive cultural, institutional, and technological challenges that shape their teaching practices and professional growth. This study investigates the professional development trajectories of EFL lecturers, focusing on how they strengthen pedagogical competence and construct professional identity across diverse institutional settings. It also identifies key factors that support or hinder their development. The study employed focus group discussions with 20 EFL lecturers from four Islamic higher education institutions, three in Aceh and one in West Sumatra, Indonesia. Five lecturers from each institution participated, sharing their experiences, strategies, and challenges related to professional development. The data were analyzed using the standard procedure of qualitative research, which involves open, axial, and selective coding. The findings revealed that lecturers enhance their pedagogical competence through various avenues, including pursuing doctoral degrees and participation in academic activities such as seminars, workshops, conferences, research, and scholarly publications. These efforts contribute significantly to the development of their professional identity. However, lecturers face persistent challenges, including financial limitations, fluctuating motivation, and limited institutional support. This study underscores the complexity of professional development for EFL lecturers within Islamic higher education settings. By identifying the contextual factors, practices, and barriers involved, the research offers valuable implications for educators, administrators, and policymakers seeking to design more effective and supportive EFL teacher development programs.